Barriers to Christian belief. - Griffith, Leonard, 1920- (New York, Forward Movement Publications, 1969)
Relevance of the Christian faith for the modern age outlined by a British preacher, addressed especially to the doubter lingering on the doorstep of the church.
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Apologetics